Analgesic synergism of gabapentin and carbamazepine in rat model of diabetic neuropathic pain - Abdullah Al-Mahmood, Sinan Mohammed; Che Abdullah, Shahrin Tarmizi; Nik Ahmad, Nik Nur Fatnoon; Mohamed, Abdul Hadi; Abdul Razak, Tariq (University of Benin, 2016)
Purpose: To evaluate synergy in the analgesic effects of a combination therapy of carbamazepine (CBZ) and gabapentin (GBP) in diabetic neuropathic pain. Methods: Neuropathic pain was produced in rats by a single intraperitoneal injection of streptozotocin (STZ) at 60 mg/kg. CBZ, GBP, and their combination were orally administered at varying doses (GBP 30 - 180 mg/kg; CBZ 20 - 40 mg/kg) comparable to their therapeutic doses in humans. Nociceptive responses in the diabetic rats were assessed using hot plate test. Results: Hot plate latency significantly increased with oral administration of GBP at a dose of 180 mg/kg when compared with control group (p < 0.05), while at a dose of 90 mg/kg, the increase was not significant. Oral administration of CBZ at doses of 20 and 40 mg/kg did not produce any significant impact on hot plate latency. However, a combination of GBP at 90 mg/kg and CBZ at 20 mg/kg produced significant increase in latency, compared with control group and other groups (p < 0.05), except the group that received 180 mg/kg GBP. The combination of low dose GBP 30 mg/kg and carbamazepine 30 mg/kg had no significant effect on latency (p > 0.05). Conclusion: The results obtained in this study provide useful information on the combination therapy of GBP and CBZ, which may be applied in the treatment of pain in diabetic neuropathy.